Cemaran Coliform Limbah Cair Tempe dan Air Minum Isi Ulang di Daerah Parung, Jawa Barat - Marliyah, Tiah; Syafriana, Vilya (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Tempeh is a food source of vegetable protein that is produced from the fermentation process. The manufacturing process of tempeh will produce solid waste and liquid waste. The solid waste from tempeh is usually used for animal feed, while the liquid waste flows into the river. Sub Parung district has some food industries, one of which is the tempeh industry and a refill drinking water depot near the tempeh factories. This study aims to determine whether the liquid waste from tempeh and the refill drinking water in the region was contaminated by Coliform bacteria. The samples used in this study were tempeh liquid waste from the tempeh X factory and drinking water from the refill drinking water depot. This qualitative descriptive study used the Most Probable Number (MPN) method. The results showed that the sample of refill drinking water did not contaminated with bacteria, but the tempeh liquid waste sample contained E. coli and Coliform bacteria with a total Coliform of about 6.2/100 mL. These findings indicate that the DAMIU found near the tempeh factories is safe to consume.